Advocating for language equity: a community-public health partnership - Dana Kurlander; Amy G. Lam; Elizabeth Dawson-Hahn; Elizabeth Dawson-Hahn; Diego de Acosta (Frontiers Media S.A., 2023)
In the United States, 21.5% of individuals aged 5 or older speak a language other than English at home and 8.2% have Limited English Proficiency (LEP). LEP individuals experience healthcare disparities, including lower access to healthcare services, poorer health outcomes, and higher levels of uninsurance. The COVID-19 pandemic highlighted and exacerbated these health disparities and unmet healthcare needs. In Alameda County (CA), where 46% of foreign-born residents speak a language other than English at home, community-based organizations have been crucial in providing translated materials and one-on-one support to ensure LEP residents receive critical COVID-19 updates and services. Refugee and Immigrant Collaborative for Empowerment (RICE) is a multilingual coalition of seven Alameda County community-based organizations led by the Korean Community Center of the East Bay (KCCEB). During the COVID-19 pandemic, RICE expanded its public health role to fill service and information gaps, advocate on behalf of LEP groups, and build a linguistically and culturally responsive public health safety network. This community case study describes a three-part advocacy-focused intervention that RICE undertook from September 2021 to October 2022. It included (1) a community needs survey, (2) a landscape assessment of the Alameda County Health Department's (ACPHD) communication materials and online platforms, and (3) relationship building with the ACPHD. The community survey revealed differences across LEP subgroups and highlighted the importance of gathering data disaggregated by language preference. The landscape assessment allowed RICE to understand the ACPHD's decision-making process and develop data-informed advocacy requests on behalf of LEP communities. Effective communication and coordination between RICE and the ACPHD shortened the feedback loop between public health authorities and LEP communities and laid the groundwork for the RICE organizations to be part of the ACPHD's future decision making. Data disaggregation, language equity-based advocacy, and cross-sector collaboration were critical ingredients in RICE's intervention. RICE's partnership and relationship of mutual accountability with the ACPHD may provide a useful model for other community-based organizations and public health departments seeking to form similar partnerships.